Discretionary Authority and Prioritizing in Government Agencies - Maarten Pieter Schinkel; Lukás Tóth; Jan Tuinstra (Tinbergen Institute, 2015)
Government agencies typically have a certain freedom to choose among different possible courses of action. This paper studies agency decision-making on priorities in a principal-agent framework with multi-tasking. The agency head (the principal) has discretion over part of the agency's budget to incentivize his staff (agents) in the pick-up of cases. The head is concerned with society's benefits from the agency's overall performance, but also with the organization's public image as formed from its case record and various non-case specific activities. Based on their talent and the contracts offered by the head, staff officials choose which type of task to pursue: complex major, yet difficult to complete cases with an uncertain outcome, or basic minor and simple cases with a much higher probability of success. The size of the agency's discretionary budget influences no t only the scale, but also the type of tasks it will engage in. Social welfare is non-monotonic and discontinuous in the agency's budget. Small changes in the budget may cause extensive restructuring from major to minor tasks, or vice versa. A budget cut can improve welfare more than extra budget would, even if resources are below the welfare-maximizing level. For lower binding budgets, the head continues to suboptimally incentivize work on complex tasks, when the agency should have shifted down to simpler tasks. Yet a reluctant head may need to be nudged with more resources to pursue productive cases. In determining the discretionary space of the agency head, government can limit the extraction of resources, but thereby also benefits less from the head's expertise. Antitrust authorities serve as one illustration of policy implications for institutional design.
Keywords: D02; H11; L44; M52; 330; Government agency; discretion; budget; enforcement priorities; antitrust